Near-infrared spectroscopy as a tool for driving research. Issue 3 (3rd March 2016) - Liu, Tao; Pelowski, Matthew; Pang, Changle; Zhou, Yuanji; Cai, Jianfeng
Abstract: Driving a motor vehicle requires various cognitive functions to process surrounding information, to guide appropriate actions, and especially to respond to or integrate with numerous contextual and perceptual hindrances or risks. It is, thus, imperative to examine driving performance and road safety from a perspective of cognitive neuroscience, which considers both the behaviour and the functioning of the brain. However, because of technical limitations of current brain imaging approaches, studies have primarily adopted driving games or simulators to present participants with simulated driving environments that may have less ecological validity. Near-infrared spectroscopy (NIRS) is a relatively new, non-invasive brain-imaging technique allowing measurement of brain activations in more realistic settings, even within real motor vehicles. This study reviews current NIRS driving research and explores NIRS' potential as a new tool to examine driving behaviour, along with various risk factors in natural situations, promoting our understanding about neural mechanisms of driving safety. Practitioner Summary: Driving a vehicle is dependent on a range of neurocognitive processing abilities. Near-infrared spectroscopy (NIRS) is a non-invasive brain-imaging technique allowing measurement of brain activation even in on-road studies within real motor vehicles. This study reviews current NIRS driving research and explores the potential of NIRS as a new tool to examine driving behaviour.